1985
DOI: 10.1073/pnas.82.6.1731
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport protein is structurally and immunologically related to band 3 and senescent cell antigen.

Abstract: Senescent cell antigen, a polypeptide that appears on the surface of senescent and damaged cells, has been shown to be derived from band 3. In the present study, the relationship between the as yet unidentified glucose transporter and senescent cell antigen is examined. Since cytochalasin B is a specific and potent competitive inhibitor of glucose transport in human erythrocytes, the glucose transport carrier was isolated by affinity chromatography on cytochalasin B-Sepharose 4B columns and eluted with D-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The absence of reduction of ouabain binding to brain capillaries [94] presents an argument against nonspecific degeneration but rather for involvement of specific mem brane proteins in Alzheimer's disease. Presently available cDNA data do not indi cate a homology between the erythrocyte an ion and glucose transport proteins [82,95], However, not only the aberrant glucose transport characteristics of red blood cells containing altered band 3 molecules [41,42,75], but also the marked glucose hypometabolism in caudate and putamen of patients with neuroacanthocytosis [96], a disease in which erythrocyte band 3 is clearly altered [42], confirm earlier immunological and structural indications for an intimate func tional relationship between these two mem brane proteins [97], In preliminary studies, we found an increase in cytochalasin B bind ing to erythrocytes from an Alzheimer pa tient, which also showed an increased amount of cell-bound IgG and altered sulfate transport characteristics (data not shown). These findings warrant further investiga tions on function and structure of the glu cose transporter in the central nervous sys tem and in erythrocytes (and other periph eral cells) of Alzheimer patients.…”
Section: Other Transport Systemsmentioning
confidence: 53%
“…The absence of reduction of ouabain binding to brain capillaries [94] presents an argument against nonspecific degeneration but rather for involvement of specific mem brane proteins in Alzheimer's disease. Presently available cDNA data do not indi cate a homology between the erythrocyte an ion and glucose transport proteins [82,95], However, not only the aberrant glucose transport characteristics of red blood cells containing altered band 3 molecules [41,42,75], but also the marked glucose hypometabolism in caudate and putamen of patients with neuroacanthocytosis [96], a disease in which erythrocyte band 3 is clearly altered [42], confirm earlier immunological and structural indications for an intimate func tional relationship between these two mem brane proteins [97], In preliminary studies, we found an increase in cytochalasin B bind ing to erythrocytes from an Alzheimer pa tient, which also showed an increased amount of cell-bound IgG and altered sulfate transport characteristics (data not shown). These findings warrant further investiga tions on function and structure of the glu cose transporter in the central nervous sys tem and in erythrocytes (and other periph eral cells) of Alzheimer patients.…”
Section: Other Transport Systemsmentioning
confidence: 53%
“…The glucose transport pro tein, which is the larger of the two molecules, apears to include all of the transmembrane region of band 3, whereas senescent cell anti gen appears to contain only approximately a third of that region [50,52]. Thus, the glucose transporter that supplies energy to cells and senescent cell antigen that terminates the life of cells appear to be related polypeptides based on immunologic and structural data.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the enhancement of Na + /K+ -ATPase, which seems to be closely related to growth stimulation (Saishu et al, 1985), is supposed to result from either an unmasking or a n activation of the enzyme, probably by a n increased Na' influx as occurs, e.g., through amiloride-sensitive channels (Levine et al, 1965;Fine et al, 1985) or furosemidesensitive routes (Paris and Pouyssegur, 1986). Thus sodium influx could act as a trigger for the activation of the Na + / K i -ATPase (Leister et al, 1985;Frantz et al, 1981), which in turn, by its association with cytoskeletal elements (Geny et al, 1982;Balaban and Bader, 1984;Kay, 1985) and by concommittant shifts in pH and ionic composition, may stimulate DNA synthesis (Pouyssegur et al, 1985) by one or another mechanism suggested by Racker (19761, Kajstura andKorohoda (1982), or Bereiter-Hahn (1988). The changes observed when cultures become confluent could be related to restriction of cellular motility; the subsequent decrease of Na +/K+-ATPase activity corresponds well with the activity decrease of this enzyme in contact-inhibited cells (Lelievre et al, 1971;Elligsen et al, 1976).…”
Section: )mentioning
confidence: 99%